Discussing the Effects of Climate Change and Urbanization through Flood Disaster in Riverside Settlements - Zeynep Özdemir; Merve Özkaynak Yolcu (Doğal Afetler ve Çevre Dergisi)
Climate change-induced floods and flood disasters pose a serious threat to many settlements on a global scale. These disasters not only cause great damage to human life and economic activities, but also adversely affect the built environment. Factors such as increased rainfall due to climate change, destruction of agricultural lands and forest areas, infrastructure deficiencies, unpreparedness of settlements for natural disasters, wrong positioning and unplanned construction are effective in the occurrence of flood disasters. Therefore, in order to prevent flood disasters, it is necessary to adopt an integrated disaster management approach and develop effective and sustainable solutions in order to increase the flood resistance of settlements, especially on the banks of rivers, and to reduce the impacts against possible disasters. In this study, firstly, the floods that occurred in Bozkurt, Ayancık and İnebolu-Özlüce in 2021 were analyzed. Based on these findings, the causes of flood disasters that occurred in Inebolu in 2022 and 2023 were investigated in the field research section. Qualitative data analysis method was used as a method in the study. In addition, in the examination of the sample areas, the damages were examined through observation with the help of photographs. Flood hazard risks were examined in accordance with the flood management plans in the sample areas determined within the scope of the study and problems were identified as a result of the findings obtained. The identified problems were evaluated within the scope of planning, design principles and legal and administrative framework. As a result, recommendations are presented for making river coastal settlements resistant to flood disasters.